Islam Dan Masyarakat Pluralistik Indonesia Dalam Perspektif Dakwah - Mustofa, Muhamad Bisri; Fauzi, Machfudz; Hidayat, Rahmat; Wuryan, Siti (Dakwah, 2022)
Da'wah and society are complementary sides of the coin in the process of Islamic da'wah. Da'i and the community who are both elements of da'wah become vital objects in the process of success of da'wah. Da'wah that is oriented to an individual piety and generally social must pay attention to things that are very urgent, namely the local wisdom of the local community. For example in the hegemony of the struggle and the long journey of da'wah in Indonesia, which lives with the heterogeneity of society and the majority is Muslim and has religious characteristics. Differences in race, ethnicity, culture, ethnicity, language, and accent from various regions are used as the foundation and fundamental value of religious religiosity as a belief. As a form of purification and for the effectiveness of the implementation of da'wah, every da'wah interpreter or dai must rely on the texts of the Qur'an and Hadith. Expertise in an effort to respond to the conditions of the community that he will preach is a form and management of da'wah that must be organized from a da'wah interpreter. In addition, the Indonesian people have a plural society structure. Then if every dai or da'wah interpreter pays attention to the conditions of this very pluralistic society, it will certainly affect all kinds of da'wah strategies that will be launched to the community. The needs and desires of the diverse plural society in discussing religion must be considered and able to be captured by the da'wah interpreter in concocting his da'wah so that it reaches a pluralistic society like Indonesia. And such da'wah should be a special concern of da'wah activists and each da'i is expected to be able to carry out his da'wah to be able to maximize the aspect of religious development for the people. So there are various Islamic studies that can be used as a stepping stone in determining the direction of da'wah, especially in Islamic society and in general pluralistic society in Indonesia. The conception of da'wah that includes the social, cultural, emotional arguments of the community is expected to be able to answer all the challenges of da'wah in the pluralistic body of society. It is used as a form to build an ideal society khoirul ummah as a form of manifestation of the development of the ummah firmly. The nature of Islam that the lil a'lamin is felt to be enough can be an injection that the empowerment of the Muslim community both mentally and spiritually in the effort to realize the welfare and unity of the ummah is very appropriate. Other forms are religious social and national social. These are the pluralistic values ​​embraced by the majority of Indonesian society.